Antibacterial amphiphiles based on ε-polylysine: synthesis, mechanism of action, and cytotoxicity. Issue 85 (16th September 2015) - Dai, Xiaomei; An, Jinxia; Wang, Yanan; Wu, Zhongming; Zhao, Yu; Guo, Qianqian; Zhang, Xinge; Li, Chaoxing
<x xml:space="preserve">Abstract</x> To combat antibiotic-resistant bacteria, an amphiphile based on ε-polylysine was synthesized via an alkylation reaction. The positively charged amphiphile could adsorb bacterial membranes, disrupt them and subsequently kill the bacteria.